As argumentações do TST sobre doenças ocupacionais nas trabalhadoras do setor frigorífico sob o prisma do materialismo histórico e dialético - Nascimento, Cláudia Cristina do (2022)
This research proposes an analysis of the justification discourses about the damage caused by occupational diseases to workers in the cold industry. From a theoretical point of view, this work aims to understand the role played by women in society by considering the production mechanism imposed by the capitalist system and to identify how systemic and articulated inequalities in the sexual division of labour influence labour relations, mainly in the refrigerators sector. In order to carry out such study, at the first moment is presented the reason why the dialectical historical materialism method was chosen, to understand the role of women in society, it is necessary to assimilate how the commodification of labor and gender inequalities (men and women) in contemporary society are triggered and articulated. It is further examined that the sexual division of labour imposes a place of social marginalisation on women class workers, since it is considered by the principle of hierarchy that male labour has more value than female labour, and by the principle of separation that there are works that are intended for women and those intended for men. Methods of organising work in refrigerators also involve the sexual division of labour, because the female workforce is destined to certain sectors of the production line and this apartment is made from a historical contextualization that care works and household tasks are naturally intended for women finally, the third part of the work whether to analyze whether the judges on the involvement of occupational diseases in cold industry workers consider the reality faced by working class women both in precarious working conditions and in coping with work overload with the double journey. It is concluded, in this work, that the decisions of the Superior Labor Court (TST) on the subject are universal, and can be applied to both women and men, with speeches of justification based on technical and legal contents. .